Sengketa Wilayah Zona Ekonomi Eksklusif Indonesia (Studi Kasus Klaim Cina Atas Laut Natuna Utara) - Ardila, Ririn; Putra, ak (Faculty of Law, Universitas Jambi, 2020)
Abstract Natuna Utara Sea is the Exclusive Economic Zone of Indonesia which is located in the Riau Islands Province, namely Natuna District. the emergence of territorial dispute in the Natuna Utara Sea due to Cina's claim on to nine-dash line. This research discusses whether Cina's claim of the nine-dash line over the North Natuna Sea complies with the 1982 UNCLOS provisions and examines Indonesia's attitude towards Cina's claims in the North Natuna Sea. The type of research used is Normative with statue approach, historical approach, and case law approach. The results of the study conclude that Cina's claims on the nine-dash line against theNatuna Utara Sea are contradictory and irrelevant according to UNCLOS 1982 and Indonesia considers that Indonesia does not have any disputes with Cina.